2023
DOI: 10.1111/nph.19122
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on cross‐kingdom RNA interference in mutualistic symbioses

Abstract: SummaryRNA interference (RNAi) is arguably one of the more versatile mechanisms in cell biology, facilitating the fine regulation of gene expression and protection against mobile genomic elements, whilst also constituting a key aspect of induced plant immunity. More recently, the use of this mechanism to regulate gene expression in heterospecific partners – cross‐kingdom RNAi (ckRNAi) – has been shown to form a critical part of bidirectional interactions between hosts and endosymbionts, regulating the interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Building on the breadth of knowledge in plant pathosystems, the interest on ckRNAi has also moved toward mutualistic interactions (Qiao et al ., 2023): The first evidence for ckRNAi in such an interaction was described in the root nodule symbiosis where tRNA‐derived sRNA fragments (tRFs) from Bradyrhizobium japonicum were found to hijack soybean AGO1 to target root development genes essential for nodule formation (Ren et al ., 2019). Similarly, tRFs from Rhizobium tropici , that target Phaseolus vulgaris genes also implicated in nodules, were shown to immuno‐precipitate with the P. vulgaris AGO5 (Sánchez‐Correa et al ., 2022).…”
Section: Is There Cross‐kingdom Rnai In the Am Symbiosis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the breadth of knowledge in plant pathosystems, the interest on ckRNAi has also moved toward mutualistic interactions (Qiao et al ., 2023): The first evidence for ckRNAi in such an interaction was described in the root nodule symbiosis where tRNA‐derived sRNA fragments (tRFs) from Bradyrhizobium japonicum were found to hijack soybean AGO1 to target root development genes essential for nodule formation (Ren et al ., 2019). Similarly, tRFs from Rhizobium tropici , that target Phaseolus vulgaris genes also implicated in nodules, were shown to immuno‐precipitate with the P. vulgaris AGO5 (Sánchez‐Correa et al ., 2022).…”
Section: Is There Cross‐kingdom Rnai In the Am Symbiosis?mentioning
confidence: 99%
“…Considering the intimate nature of the interaction between plants and AM fungi, another challenge will be to understand whether silencing competent sRNAs are exchanged between the symbiotic partners of AM in both directions (Qiao et al ., 2023). The validation of in silico predicted targets of sRNA‐mRNA pairs is a key goal to be achieved to provide convincing evidence on the presence of ckRNAi.…”
Section: Open Questions and Future Perspectivesmentioning
confidence: 99%
“…EVs have been observed in apoplastic wash fluids (AWF) derived from various plant parts -leaves, roots, imbibing seeds, pollen, and fruits Cai et al 2018;Ju et al 2013;Prado et al 2014). In plant-microbe interactions, evidence is accumulating to suggest the involvement of EVs in the mutual manipulation of plant hosts and their colonizing microbes (Cai et al 2021;Qiao et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Various types of cargo molecules, including nucleic acids (Ruf et al 2022), proteins (He et al 2021), and cell wall components (La Canal & Pinedo 2018;Bellis et al 2022) have been found in association with EVs. Small RNAs of 18-25 nucleotides in size are frequently described as associated with EVs and are thought to mediate mutual cross-kingdom gene silencing in pathogenic (Cai et al 2019) and mutualistic (Qiao et al 2023) plant-microbe encounters. Apart from canonical small RNAs, circular RNAs (Zand Karimi et al 2022), rRNA fragments (Kusch et al 2023;Panstruga & Spanu 2024) and mRNAs (Kwon et al 2021;Ruf et al 2022;Wang et al 2024) have been linked to these vesicles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation